PENERAPAN MODEL PEMBELAJARAN KOOPERATIF LISTENING TEAM UNTUK MENCAPAI KETUNTASAN BELAJAR SISWA PADA POKOK BAHASAN KESETIMBANGAN KIMIA DI KELAS XI IPA SMA NEGERI 12 PEKANBARU - Erna, Maria; ', Nur Aini; ', Rini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Research has been done to get student’s mastery learning with by using model Cooperative Listening Team inclass XI Science SMAN 12 Pekanbaru. This research is pra-experimentre search with one-shot study case design. The sampel use random from the four class XI Science. This research was conducted in class XI Science IPA 4, the for two month’s from november to desember 2014. Data analysis technique by using five formula mastery: mastery individual learning objectives (KTPI), mastery each of the learning objectives (KMTP), classical mastery learning objectives (KTPK), mastery learning of individual (KI), mastery learning classical (CBC). Research for the final show that classical mastery learning objectives 80% and mastery learning classical is 91,667%. It’s means that the application of cooperative learning model of Listening Team can achieve student’s mastery learning on the subject of chemical equiblirium inclass XI IPA SMAN 12 Pekanbaru.Key Words: Listening Team, mastery learning, chemical equilibrium